SPECIFICITY OF SCIENCE IN THE CONTEXT OF ITS MORAL DIMENSION (CIVILIZATION ASPECT) - Skyba, Ivan (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The relevance of the research is determined by the ambivalence of applying scientific knowledge, which can bring humanity good and great harm. However, the issue is not science or scientific knowledge itself, but in whose hands it is, what social interests are behind it, what social and state structures direct its development, and according to which values. That is, the answer to the questions of the strategic development of science must certainly lie in its value, and moral dimension. The aim and tasks are a study of the specifics of science in the context of its moral dimension in the conditions of modern civilizational progress of mankind. Research methods. The methodological strategy of the research is based on socio-cultural, cultural-historical, systemic, and comparative methodological approaches in their dialectical unity. Research results. It is important that science, as a part of the culture, is guided by socio-cultural values in its development and does not lose touch with the real history of society. The problem of the relationship between science and morality is correlated with the relationship between science and practical activity. This problem also actualizes the social responsibility requirement of the scientific community not only for the direct result of the research but also for its practical use in various subsystems of society and social life. Science needs social control to be oriented to the service of social progress because, beyond social and moral use, scientific knowledge loses its cultural and humanistic dimension. Discussion. In the discussion, the author examines the issue of the relationship between science and religion, which is an important component of the issue of the relationship between science and morality. Conclusion. The main value criterion of modern scientific knowledge is the emphasis on the awareness of the socially significant limits of theoretical research, supplementing it with cultural and ethical parameters and humanistic guidelines. The value imperative largely determines the specifics of the professional ethics of the scientist himself, in particular, it presents a number of requirements for the ethics of the process of scientific creativity and dictates some moral norms of the scientist’s creative activity. It is worth remembering that science is not an end in itself, it must serve man, his good.